Bioisosteric modification on melatonin: synthesis of new naphthalene derivatives, in vitro antioxidant activity and cytotoxicity studies (Brazilian Journal of Pharmaceutical Sciences, 2020)
Melatonin (MLT) is a strong free radical scavenger that protects the body from the deleterious effects of excess oxidants. Synthesis of MLT analogue compounds with antioxidant potency has recently attracted the interest of researchers. In general, the strategy consists of modifying the groups in the different sites of the indole ring or replacing the indole ring with an analogue. As part of our ongoing research, the antioxidant capacity and cytotoxicity of newly synthesized MLT analogue naphthalene derivatives were evaluated. The radical scavenging activity was tested by a 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay. Most of the synthesized compounds showed significant antioxidant activity in comparison to MLT. The structure-activity relationship was identified. The in vitro cytotoxic effects of the synthesized compounds were also investigated in CHO-K1 cells using the MTT assay.